Russian Orthodoxy Nowadays - V. N. LEKSIN (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2018)
Russian Orthodoxy is one of the most mythologized and difficult for scientific research fragments of modern Russia’s social life. Thus, the statements still exist on the universal Orthodoxy of the Russian people, because the State statistics does not really characterize a condition of the population or its different groups religiosity (rare exception is few indicators in the reports on periodical population census). Moreover, the researcher constantly faces polar estimates of the same situations in Russian Orthodoxy, both in publications of its irreconcilable opponents and apologists, while analysis of dichotomy “religiosity/ secularism” often goes beyond the boundaries of scientific discussions. At the same time these difficulties shouldn’t be overestimated. Splendid works by domestic sociologists have emerged that characterized actual religiosity of our contemporaries, formation of Church statistics has begun, reliable information on real events in Orthodox life have begun to be published regularly in the materials of cathedral and diocesan assemblies, Orthodox mass-media are becoming more and more informative and analytical (including Internet) and so on. Euphoria in connection with religious life legalization in Russia is passing off, the attitude to what is taking place in the sphere of Russian Orthodox Church (ROC) – the clergy and laity – is becomingmore realistic, while problematic situations are becoming an object of open discussions and for the most part of them appropriate solutions are being found. Along with all the unshakeable fundamentals of Orthodoxy, dynamism of modern Orthodoxy life is very high, as it is shown in the article. Russian Orthodoxy goes far and in various ways beyond Church boundaries. In the article an attempt is made to throw light on just several aspects of this phenomenon. These are estimates of a number of people leading an Orthodox way of life, parameters of rapid expansion of Church institutions and increase of the clergy number, innovations in Church education, ROC’s attitude to non-Orthodoxy and adherence to different faith, problems of real separation of Church and State and the place of Orthodoxy in modern culture. ROC’s role in social and political life of Russia is clearly in contrast with the situation in a number of Western countries and it seems to be one of significant but unfortunately, weakly accented problems of modern politological analysis.